The Use of High-Quality Watermelon Seedlings Is Prerequisite to Limit the Transplanting Shock and Achieve Yield Earliness - Filippos Bantis; Athanasios Koukounaras (Horticulturae, 2023)
One of the most important crops of the Mediterranean, watermelon (Citrullus lanatus), is almost exclusively established through seedlings. For many years, agronomists, nurseries, and farmers have aimed to produce and use high-quality seedlings for better growth in the field. However, seedling quality has not been examined as to what defines the subsequent plant, flower, and fruit development, and to what extent. Our aim was to test whether different seedling qualities labeled as “Optimum”, “Acceptable”, or “Not Acceptable” for cultivation actually perform variably in terms of vegetative, flowering, and fruit development, as well as fruit quality after a full growing cycle in the field. Vegetative growth (stem diameter, plant area, and leaf number) was evaluated until flowering and was enhanced for Optimum plants. The flowering of Not Acceptable plants started two days later, while Optimum plants retained a greater number of female flowers throughout the two-week blooming evaluation. Most importantly, Optimum plants developed mature fruits four and six days faster than the Acceptable and Not Acceptable ones, respectively, showing considerable yield earliness. The photosynthetic mechanism, as well as fruit morphology and phytochemical content, were not affected by quality categories. Overall, indeed it is important to use high-quality seedlings to achieve yield earliness of watermelon fruits.